2021
DOI: 10.1002/jrs.6210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers on kidney failure by Raman spectroscopy

Abstract: Chronic kidney disease (CKD) is a global health problem. Our study employed Raman spectroscopy for the first time to analyze potential biomarker such as tryptophan (Trp) on kidney failure and show the difference between normal and CKD groups. Adenine model of CKD characterized most of the physiological changes observed in human CKD. For that, 6‐week‐old Wistar male rats were assigned to the two groups: the control group, 0.5% carboxymethyl cellulose (CMC) was administered; the CKD group, adenine was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Raman peaks for component 2 included 1366, 1372, 1437, and 1445 cm -1 , which mainly arose from lipids [7] . The identified Raman peaks are consistent with those reported in previous studies of the kidney under various conditions [52][53][54][55] . While the MCR-ALS analysis of RSI images provides an important starting point for understanding the classes of compositional contributors and their spatial distribution, it does not offer definitive confirmation of the specific molecules in the tissue sample, making the integration with MALDI MSI particularly significant and insightful.…”
Section: Biological Sample: Kidney Tissuesupporting
confidence: 90%
“…Raman peaks for component 2 included 1366, 1372, 1437, and 1445 cm -1 , which mainly arose from lipids [7] . The identified Raman peaks are consistent with those reported in previous studies of the kidney under various conditions [52][53][54][55] . While the MCR-ALS analysis of RSI images provides an important starting point for understanding the classes of compositional contributors and their spatial distribution, it does not offer definitive confirmation of the specific molecules in the tissue sample, making the integration with MALDI MSI particularly significant and insightful.…”
Section: Biological Sample: Kidney Tissuesupporting
confidence: 90%
“…The strongest peak in urine is 1005 cm −1 which corresponds to the N-C-N stretching in urea [ 46 ]. Certain peaks at 1359, 1554, and 1636 cm −1 can be attributed to specific amino acids [ 47 ]. For instance, the peaks at 1355, 1551, and 1610 cm −1 are attributed to tryptophan [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy and surface enhanced Raman scattering (SERS) have been used in the analysis of biological fluids, including blood ( Berger et al, 1999 ; Enejder et al, 2002 ), urine ( Premasiri, Clarke & Womble, 2001 ; Moreira et al, 2017 ), saliva ( Virkler & Lednev, 2010 ; Hardy et al, 2022 ), and others with clinical applications ( Panikar et al, 2021 ). Recently, Raman spectroscopy was used to analyze the spectral differences of urine composition from healthy subjects and from patients with advanced kidney disease, including CKD 4/5 and ESRD ( Senger et al, 2020 ; Chen et al, 2020b , 2020a ; Gulyamov et al, 2021 ; Kamińska et al, 2022 ). These studies found that chemometric analysis of urine Raman spectral data detected molecular ‘fingerprints’ associated with advanced kidney disease ( Senger et al, 2019 , 2020 ; Chen et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%